Mitigation of nickel toxicity in rice plants by exogenous γ-aminobutyric acid: Enhancement of growth, antioxidant defense, and metal homeostasis - Zakirullah Khan; Rahmatullah Jan; Saleem Asif; Muhammad Farooq; Kyung-Min Kim (Plant Stress, 2025)
In this study, we examined the impacts of exogenously applied γ-aminobutyric acid (GABA) on rice plants under nickel (Ni)-induced stress. Nickel stress significantly reduced growth parameters, disrupted mineral balance, and increased plant stress through elevated H₂O₂, malondialdehyde (MDA), and superoxide anions (O₂⁻), coupled with compromised antioxidant defense mechanisms. However, GABA application effectively alleviated these detrimental effects by enhancing growth parameters, improving relative water content, and reducing oxidative stress. GABA significantly increased antioxidative enzymes activities such as catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX), and glutathione (GSH). Furthermore, GABA reduced nickel accumulation by upregulating metal transporter proteins (MTPs) OsMTP1 and OsMTP8, promoting nickel sequestration into vacuoles and restoring essential mineral contents, such as Ca²⁺ and Mg²⁺. Gene expression analysis revealed that GABA stimulated the GABA shunt pathway, significantly enhancing the expression of OsGAD, OsGABA-T, and OsSSADH. These findings demonstrate the potential of using GABA to mitigate nickel toxicity by modulating growth, antioxidant defenses, metal homeostasis, and stress-responsive pathways in rice plants.